Ascorbic acid modulates the structure of the Pseudomonas aeruginosa virulence factor pyocyanin and ascorbic acid-furanone-30 combination facilitate biofilm disruption - Das, Theerthankar; Das, Biswanath; Young, Brandon Clark; Aldilla, Vina; Sabir, Shekh; Almohaywi, Basmah; Willcox, Mark; Manefield, Mike; Kumar, Naresh (Frontiers in Microbiology, 2023)
The production of pyocyanin by Pseudomonas aeruginosa increases its virulence, fitness and biofilm formation. Pyocyanin is also a redox molecule and we hypothesize that ascorbic acid being an antioxidant will interact with pyocyanin. The main objective of this study was to investigate the potential interaction of ascorbic acid with pyocyanin, and also to investigate the impact of ascorbic acid in combination with Furanone-30 on quorum sensing and biofilm formation of P. aeruginosa. When incubated with ascorbic acid, hyperchromic and hypsochromic shifts in pyocyanin absorbance peaks at 385 nm and 695 nm were observed. In the presence of dehydroascorbic acid and citric acid, these shifts were absent, indicating that the intrinsic antioxidant property of ascorbic acid was probably essential in binding to pyocyanin. NMR spectroscopy showed shifts in 1H NMR pyocyanin peaks between 8.2 to 5.8 ppm when incubated in the presence of ascorbic acid. Density Functional Theory (DFT) supported potential interactions between the –CH2OH or –OH moieties of ascorbic acid with the –C=O moiety of pyocyanin. The pyocyanin-ascorbic acid complex impaired pyocyanin binding to DNA. Ascorbic acid combined with furanone-30 elevated quorum-sensing inhibition in P. aeruginosa, which was directly associated with significantly reduced P. aeruginosa virulence, adhesion, aggregation and biofilm formation and enhanced antibiotic-mediated bacterial killing. This study demonstrated that the antioxidant ascorbic acid directly binds to pyocyanin, modulates its structure and results in disruption of biofilm formation and associated tolerance to antibiotics.